Efektivitas Dan Efisiensi Belanja Daerah Untuk Pembangunan Manusia Dan Pengentasan Kemiskinan Di Provinsi Papua - Kende, Tutun A.; Hafizrianda, Yundy; Ngutra, Risky Novan (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
This study aims to analyse the effectiveness and efficiency of regional spending on human development and poverty alleviation in Papua Province. We conducted this research in the context of districts and cities across Papua Province. The study utilized secondary data sourced from the Central Statistics Agency of Papua Province and the Ministry of Finance of the Republic of Indonesia, covering the period from 2010 to 2022. The data analysis method employs data envelope analysis (DEA) to measure the efficiency level of regional spending, as well as panel data regression analysis to analyse the effectiveness and influence of regional spending on human development and poverty alleviation. The study's findings show that, in general, regional spending in districts and cities throughout Papua Province is inefficient. Only a few districts and cities efficiently allocate regional spending for human development and poverty alleviation. Furthermore, the average regional expenditure is effective and has a positive effect on the human development index in districts and cities throughout Papua province; only Jayapura city has a significant effect on the human development index. While the average regional expenditure is effective and has a negative effect on the percentage of poor people in districts and cities throughout Papua province, only Intanjaya, Jayawijaya, and Nduga districts have no significant effect on the percentage of poor people.